Ancient Christians and the power of curses: magic, aesthetics, and justice - Nasrallah, Laura Salah (Cambridge University Press, 2024)
"Ancient Christians lived in a world of "magic." They and others-particularly those of low status-used curses as ritual objects to seek justice from gods and other beings. These curses, and invective against them, reveal the complexity of ancient Mediterranean religions and their aesthetics: their use of materiality, poetics, song, and incantation"--